Self-triggered continuous–discrete observer with updated sampling period. (December 2015) - Andrieu, Vincent; Nadri, Madiha; Serres, Ulysse; Vivalda, Jean-Claude
Abstract: This paper deals with the design of high gain observers for a class of continuous-time dynamical systems with discrete-time measurements. Different approaches based on high gain techniques have been followed in the literature to tackle this problem. Contrary to these works, the measurement sampling time is considered to be variable. Moreover, the new idea of the proposed work is that the use of the output measurements by the observer follows an event based on an extended observer state component. Assuming that the vector fields related to the considered system are globally Lipschitz, the asymptotic convergence of the observation error is established. As an application of this approach, a state estimation problem of an academic bioprocess is studied, and its simulation results are discussed.